Effect of Organosolv Pretreatment on Delignification for Bioethanol Feedstock from Oil Palm Empty Fruit Bunch (OPEFB). (December 2018) - Mardawati, Efri; Badruzaman, Ibad; Nurjanah, Sarifah; Bindar, Yazid
Abstract: Lignin degradation of Oil Palm empty fruit bunch (OPEFB) as raw material for bioethanol production has been successfully performed by organosolv pretreatment. This paper presents the study and optimization of organosolv pretreatment on Delignification of OPEFB as raw material of bioethanol. Ethanol was used in organosolv pretreatment as the organic solvent. Organosolv pretreatment disrupted the lignocellulosic matrix to a considerable extent and increased hydrolysability of pretreated materials. Response surface methodology (RSM) was applied to determine the optimal condition operation of each significant variable, which included organic solvent concentration, reaction time, and particle size. The Box-Behnken Design (BDD) was employed to investigate the individual crucial component of the condition operation that significantly affected lignin degradation. The maximum lignin degradation was obtained 27.68% which correspond to 65% (v/v) of ethanol, with reaction time 65 min and 50 mesh of particle size. Therefore, it can be concluded that organosolv pretreatment can be used to degrade lignin from OPEFB as a bioethanol feedstock.